Loading Research of Load-Bearing Structure of Hopper Car with Composite Roof - Fomin, O. V; Lovska, A. O; Fomina, A. M; Sova, S. S (Science and Transport Progress, 2022)
Purpose. The work is aimed to investigate the loading of load-bearing structure with composite material roof. This will allow reducing the dead weight of the hopper car and will contribute to the possibility of increasing its carrying capacity. Methodology. Investigations were performed using the example of hoper car for grain transporting, model 19-6869, manufactured by Karpaty Experimental Mechanical Plant. It is important to say that the use of composite material reduces the roof weight by up to 40% in comparison with the metal design. That is why mathematical modeling of dynamic loading of the hopper car with composite roof was carried out. Differential equations were solved by Runge-Kutta method in MathCad software package. Initial conditions were assumed to be zero. During the calculations, the spring suspension parameters of the 18-100 bogie models were taken into account. The obtained results of calculations were used when determining the main indicators of the roof strength. The spatial model of the hopper car roof was created in SolidWorks software complex. Calculation was performed by the finite element method, which is implemented in the SolidWorks Simulation (CosmosWorks) software complex. When constructing the finite element model of the hopper car, the isoparametric tetrahedra were used. The optimum number of the model elements was determined by the grapho-analytical method. Findings. The basic indices of load-bearing structure dynamics of hopper car with composite roof were obtained. Acceleration of the body in the mass center was 5,0 m/s2. Coefficient of vertical dynamics is equal to 0.67. It was found that the maximum equivalent stresses in the roof for all the considered loading schemes do not exceed the admissible values, that is, the roof strength is ensured. Originality. The mathematical modeling of dynamic loading of the load-bearing structure of the hopper car with composite roof was carried out. The acceleration values as the components of dynamic loading acting on it during operation as well as vertical dynamics coefficient were determined. The strength indicators of the composite roof under the main operational loading modes have been found out. Practical value. The conducted research will contribute to the creation of guidelines for the design of innovative structures of the rolling stock, as well as increase the efficiency of its operation.